Identification of pharmacological inhibitors of conventional protein secretion. Issue 1 (December 2018) - Zhao, Liwei; Liu, Peng; Boncompain, Gaelle; Loos, Friedemann; Lachkar, Sylvie; Bezu, Lucillia; Chen, Guo; Zhou, Heng; Perez, Franck; Kepp, Oliver; Kroemer, Guido
Abstract The retention using selective hooks (RUSH) system allows to withhold a fluorescent biosensor such as green fluorescent protein (GFP) fused to a streptavidin-binding peptide (SBP) by an excess of streptavidin molecules that are addressed to different subcellular localizations. Addition of biotin competitively disrupts this interaction, liberating the biosensor from its hook. We constructed a human cell line co-expressing soluble secretory-SBP-GFP (ss-SBP-GFP) and streptavidin within the endoplasmic reticulum (ER) lumen and then used this system to screen a compound library for inhibitors of the biotin-induced release of ss-SBP-GFP via the conventional Golgi-dependent protein secretion pathway into the culture supernatant. We identified and validated a series of molecularly unrelated drugs including antianginal, antidepressant, anthelmintic, antipsychotic, antiprotozoal and immunosuppressive agents that inhibit protein secretion. These compounds vary in their capacity to suppress protein synthesis and to compromise ER morphology and Golgi integrity, as well as in the degree of reversibility of such effects. In sum, we demonstrate the feasibility and utility of a novel RUSH-based phenotypic screening assay.